Teacher´s belief level about the reform in Mathematics Education in Costa Rica - Agüero-Calvo, Dra. Evelyn (2018)
This article presents the results of a study on the level of beliefs that mathematics teachers manifest regarding reforms in mathematics education in Costa Rica started in 2013, based on the premise that the teachers’ actions respond to these levels of beliefs more than to official guidelines or theoretical approaches. For this purpose, an instrument called Measurement of teachers’ beliefs regarding the new mathematics study programs in secondary school designed, utilized and validated by Monge and Reyes (2017). A sample of 361 public day school teachers of the Ministry of Public Education of Costa Rica was used in 2017. In addition, possible differences according to sex, professional category, and years of seniority were researched. The results indicate that 57% of teachers have high belief levels about the reform, and that no differences in belief level are detected according to gender, professional category, or seniority. In addition, the study found that 65.9% of the cases consider that problem-solving is the most appropriate methodology to address the topics in the mathematics programs, and 70.4% consider that what is proposed in the new mathematics programs is not feasible to be implemented in the classrooms of the Costa Rican education system.